Cross-cultural metathemes of Chinese and Japanese university students' perspective on parental care - Peng, Xuxin; Nakatani, Hisae; Chen, Huifang; Inoue, Yuriko; Song, Fang; Yoshihara, Mikako; Lei, Ruxin (Frontiers in Public Health, 2023)
Introduction: Due to declining birthrates and aging populations, parental care is going to place a greater burden on younger generations in the future, especially in East Asia where it is more common for children to provide care regardless of whether there is a national long-term care insurance program. Therefore, it has become important to understand the younger generation's views on parental care. Methods: An explorative, metathematic qualitative study design was used. Data collection relied on semi-structured interviews, of which 19 Chinese and 19 Japanese university students were conducted from December 2021 to July 2022 using a snowball sampling method. Metatheme analysis was then used to identify broad cross-cultural metathemes and inter-relationships on parental care. Results: Three parental care metathemes were identified for the perspectives of parental care: distrust of leaving parental care to others, responsibility to care for their parents, and importance of parentchild interactions about parental care. Conclusion: To improve social support for care, both countries must improve long-term care service delivery and healthcare systems and ensure that there is a trusting relationship between healthcare professionals and the public. Governments should also ensure that adult children receive assistance to balance their work, life, and parental care responsibilities. The findings provide several practical suggestions for improving healthcare systems in China and Japan through the younger generations' views.